TreeWatch.net: A Water and Carbon Monitoring and Modeling Network to Assess Instant Tree Hydraulics and Carbon Status - Steppe, Kathy; von der Crone, Jonas S.; De Pauw, Dirk J. W. (Frontiers in Plant Science, 2016)
TreeWatch.net is an initiative that has been developed to watch trees grow and function in real-time. It is a water and carbon monitoring and modeling network, in which high-quality measurements of sap flow and stem diameter variation are collected on individual trees. Automated data processing using a cloud service enables instant visualization of water movement and radial stem growth. This can be used to demonstrate the sensitivity of trees to changing weather conditions, such as drought, heat waves or heavy rain showers. But TreeWatch.net’s true innovation lies in its use of these harmonized data to also parameterize process-based tree models in real-time, which makes displaying the much-needed mechanisms underlying tree responses to climate change possible. Continuous simulation of turgor to describe growth processes and long-term time series of hydraulic resistance to assess drought-vulnerability in real-time are only a few of the opportunities our approach offers. TreeWatch.net has been developed with the view to be complementary to existing forest monitoring networks and with the aim to contribute to existing dynamic global vegetation models. It provides high-quality data and real-time simulations in order to advance research on the impact of climate change on the biological response of trees and forests. Besides its application in natural forests, we also envision a broader societal application of TreeWatch.net by selecting trees in nature reserves, public areas, cities, university areas and schoolyards to teach youngsters and create public awareness on the effects of changing weather conditions on trees and forests in this era of climate change.